Sighting record listing, Iowa, 6/1/1999-7/31/1999, Bery Engebretsen - Engebretsen, Beryet al (1999)
An annotated list of birds sighted by Bery Engebretsen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1999. Epson - sheet feed